Aryl Sulfonium Salts for Site‐Selective Late‐Stage Trifluoromethylation. (3rd September 2019) - Ye, Fei; Berger, Florian; Jia, Hao; Ford, Joseph; Wortman, Alan; Börgel, Jonas; Genicot, Christophe; Ritter, Tobias
Abstract: Incorporation of the CF3 group into arenes has found increasing importance in drug discovery. Herein, we report the first photoredox‐catalyzed cross‐coupling of aryl thianthrenium salts with a copper‐based trifluoromethyl reagent, which enables a site‐selective late‐stage trifluoromethylation of arenes. The reaction proceeds with broad functional group tolerance, even for complex small molecules on gram scale. The method was further extended to produce pentafluoroethylated derivatives. Abstract : Das Beste zum Schluss : Eine positionsselektive Trifluormethylierung von Arenen verläuft über Arylsulfonium‐Salze als Intermediate. Viele funktionelle Gruppen werden in dieser Reaktion toleriert, die zudem die Synthese von C2 F5 ‐Derivaten wirkstoffähnlicher Verbindungen ermöglicht.